Effects of taurine supplementation in elite swimmers performance - Batitucci, Gabriela [UNESP]; Terrazas, Sara Ivone Barros Morhy [UNESP]; Nóbrega, Mariana Pereira [UNESP]; De Carvalho, Flávia Giolo; Papoti, Marcelo; Marchini, Júlio Sérgio; Da Silva, Adelino Sanchez Ramos; De Freitas, Ellen Cristini [UNESP] (FapUNIFESP (SciELO), 2018)
Aim: Taurine is considered a semi-essential amino acid characterized by having various physiological functions in the body that modulate mechanisms of action involved in the muscle contraction process, increased energy expenditure, insulin signaling pathway, carbohydrate metabolism, and scavenging free radicals. These functions are crucial for aerobic exercise performance; thus, taurine supplementation may benefit athletes' performance. The objective of this study was to evaluate the effects of taurine supplementation on the resting energy expenditure and physical performance of swimming athletes. Methods: In a double-blind study, 14 male swimmers were randomized into two groups: The taurine group (n = 7) and the placebo group (n = 7), which received 3 g per day of taurine or placebo in capsules during 8 weeks. Resting energy expenditure, plasma taurine, physical performance, anthropometry, dietary consumption were measured and an incremental test was performed to determine their maximal front crawl swimming performances before and after the 8-week period. Results: The levels of serum taurine (p < 0.0001) and lactate (p = 0.0130) showed a significant increase in the taurine group; however, the other variables were not different. No changes were observed in the resting energy expenditure, mean speed performed, and the anaerobic threshold of the swimmers post-supplementation period. Conclusion: Supplementation of taurine increased plasma concentrations of this amino acid, but did not lead to significant changes in food intake, rest energy expenditure, and athletes' performance. However, the supplemented group presented a higher lactate production, suggesting a possible positive effect of taurine on the anaerobic lactic metabolism.
Keywords: Anaerobic lactic metabolism; Energy expenditure; Swim